1988
DOI: 10.1056/nejm198804143181502
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Anticonvulsant Drugs in Patients Free of Seizures for Two Years

Abstract: We discontinued anticonvulsant drugs in 92 patients who had been free of seizures during two years of treatment with a single drug. All the patients had epilepsy that had previously been untreated, and had been randomly assigned to receive carbamazepine, phenytoin, or sodium valproate. Thirty-one patients relapsed, and 61 remained free of seizures. The mean duration of the follow-up in the patients remaining free of seizures was 35 months (range, 6 to 62). There was no significant difference between the relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
8

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(74 citation statements)
references
References 18 publications
2
64
0
8
Order By: Relevance
“…That is because there is a co-linearity between them. This variable, which is an indicator of seizure severity before control, has been shown by other studies to be a predictive factor for seizure recurrence after AED withdrawal [19][20][21] . Other studies have demonstrated that this factor has shown only a tendency towards significance 22,23 .…”
Section: Discussionmentioning
confidence: 69%
“…That is because there is a co-linearity between them. This variable, which is an indicator of seizure severity before control, has been shown by other studies to be a predictive factor for seizure recurrence after AED withdrawal [19][20][21] . Other studies have demonstrated that this factor has shown only a tendency towards significance 22,23 .…”
Section: Discussionmentioning
confidence: 69%
“…While some studies show that within the NCS/NCSE group, subjects with generalized ictal discharges had a worse prognosis compared to subjects with unilateral ictal discharges [34], others did not find any prognostic correlation with abnormal or epileptiform EEG [31]. In the context of AED withdrawal, a number of studies have identified factors associated with increased risk of relapse including multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [29,[35][36][37]. While we did not analyze outcomes based on NCS/NCSE subtypes, we did find that the primary background EEG abnormality was similar to previously published studies and did not differ between the wean and non-wean groups.…”
Section: Discussionmentioning
confidence: 99%
“…Aproximadamente dois terços das pessoas que obtiveram controle podem interromper o tratamento com DAE após período aproximado de dois anos, continuando em remissão posteriormente (Sander, 1993;Callaghan et al, 1988;Medical Research Council Antiepileptic Drug Withdrawal Study Group, 1991).…”
Section: Relevância Da Epilepsia Como Problema De Saúde Públicaunclassified